The economic effects of supplementary health insurance in Brazil: evidence from firms and labor markets - Bigliazzi, Giovana Cavaggioni (2025)
This thesis investigates the economic implications of the expansion of Employer-Sponsored Health Insurance (ESHI) in Brazil, focusing on its effects on firm performance, healthcare labor allocation, and employment quality. While Brazil\'s public Unified Health System (SUS) guarantees universal health-care access, formal-sector firms increasingly offer supplementary private health plans, resulting in a segmented system of healthcare provision tied to labor market status. Using rich administrative data from 2004 to 2017 and multiple empirical strategies, the thesis explores how ESHI shapes outcomes beyond healthcare access, including productivity, physician supply, and absenteeism. We find no significant effect of ESHI adoption on firm-level productivity (value added per worker) and profits, potentially due to short-run adjustment costs or delayed financial returns. The second paper documents a reallocation of physicians from the public to the private sector following ESHI expansion, suggesting a crowd-out effect that may weaken the public health system, driven by wage differentials and better working conditions in the private market. The third paper examines the effect of ESHI on workers\' medical leave in Brazil. Contrary to the expectation that ESHI would increase leave-taking by lowering the cost of absence, the results show a modest reduction in the probability of medical leave, coupled with a slight increase in the average duration of leave among those who take it. No significant effects are found for leaves due to workplace accidents or occupational illnesses. These findings suggest that ESHI may reduce the need for short-term absences while enabling longer recovery periods for a subset of workers. ESHI appears to improve general worker health and facilitate access to preventive care, even if it does not directly reduce work-related risks. Taken together, our findings contribute to the literature on health economics, labor markets, and public-private interactions in service provision, underscoring the multidimensional impact of ESHI in a developing country with segmented healthcare and labor markets. The results have implications for policy design in emerging economies, highlighting both the benefits and unintended consequences of expanding private health insurance coverage in contexts with dual health systems.